Model Partisipasi Masyarakat dalam Program Kota Tanpa Kumuh (KOTAKU) di Kelurahan Airlangga Kecamatan Gubeng Kota Surabaya - Muhammad Rizky Akbar; Rindawati Rindawati; Muzayanah Muzayanah (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
The focus of this research is to describe the participation model of the Airlangga Village community in the KOTAKU program. This study is essential because, empirically, community participation in the Airlangga sub-district has been going well and is sustainable in protecting the environment. It is necessary to study the model and form of participation implemented through the involvement of PUPR, local government, government partners, the private sector and the village community. Examining the internal and external factors that support collaboration, the designed collaborative model is expected to contribute suggestions for solving slum areas in other regions. Using a quantitative research approach, this study produced the following data: 1). The form of participation used by 99 respondents was 20% using thoughts, 29% using energy and 22% using expertise and 16% using materials or money. 2). The collaboration model used by the Airlangga sub-district is 4-Key or 4K, namely Institutionalism, Citizen Control, Facilitative Leadership and Communication. 3) Factors that influence community participation are age, gender and level of education. External factors that influence community participation are communication, leadership and the role of the facilitator